Mathematical Modeling and Simulation of Photovoltaic Cell using Matlab-Simulink Environment - J.Surya Kumari; Ch. Sai Babu (Institute of Advanced Engineering and Science, 2012)
Photovoltaic power supplied to the utility grid is gaining more and more visibility while the world’s powers demand is increases. Growing demand, advancements in semiconductor technology and magnetic materials such as high frequency inductor cores, has a significant impact on PV inverter topologies and their efficiencies, on the improvement of the control circuits on the potential of costs reduction. The user naturally wants to operate the Photovoltaic (PV) array at its highest energy conversion output by continuously utilizing the maximum available solar power of the array. The electrical system PV modules are powered by solar arrays requires special design considerations due to varying nature of the solar power generated resulting from unpredictable and sudden changes in weather conditions which change the solar irradiation level as well as the cell operating temperature. This paper, a mathematical model of a Photovoltaic (PV) cell used matlab-simulink environment, is developed and presented. The model is developed using basic circuit equations of the photovoltaic solar cells including the effects of solar irradiation and temperature changes. The main objective is to find the parameters of the nonlinear I–V equation by adjusting the curve at three points: open circuit, maximum power, and short circuit. the method finds the best I–V equation for the single-diode photovoltaic (PV) model including the effect of the series and parallel resistances– Key words : Photovoltaic system (PV), maximum power, PV array,PV cellDOI:http://dx.doi.org/10.11591/ijece.v2i1.117